Understanding Burkholderia glumae BGR1 Virulence through the Application of Toxoflavin-Degrading Enzyme, TxeA - Namgyu Kim; Duyoung Lee; Sais-Beul Lee; Gah-Hyun Lim; Sang-Woo Kim; Tae-Jin Kim; Dong-Soo Park; Young-Su Seo (Plants, 2023)
Rice (Oryzae sativa cv. dongjin) is a cornerstone of global food security; however, Burkholderia glumae BGR1, which is responsible for bacterial panicle blight (BPB), threatens its productive output, with dire consequences for rice and other crops. BPB is primarily caused by toxoflavin, a potent phytotoxin that disrupts plant growth at various developmental stages. Therefore, understanding the mechanisms through which toxoflavin and BPB affect rice plants is critical. Toxoflavin biosynthesis in B. glumae BGR1 relies on the toxABCDE operon, with ToxA playing a central role. In response to this threat, our study explores a metagenome-derived toxoflavin-degrading enzyme, TxeA, as a potential defense mechanism against toxoflavin’s destructive impact. TxeA-induced degradation of toxoflavin represents a potential strategy to mitigate crop damage. We introduce a groundbreaking approach: engineering transgenic rice plants to produce toxoflavin-degrading enzymes. These genetically modified plants, armed with TxeA, hold significant potential for combating toxoflavin-related crop losses. However, removal of toxoflavin, a major virulence factor in B. glumae BGR1, does not completely inhibit virulence. This innovative perspective offers a new shift from pathogen eradication to leveraging transgenic plants’ power, offering a beacon of hope for crop protection and disease management. Our study offers insights into the intricate interplay between toxoflavin, BPB, and TxeA, providing a promising avenue to safeguard rice crops, ensure food security, and potentially enhance the resilience of various agricultural crops to B. glumae BGR1-induced diseases.